The Complete Works of Artemus Ward $1 (BPart 4: To California and Returns - Ward, Artemus, 1834-1867 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Complete Works of Artemus Ward $1 (BPart 4: To California and Return" by Charles Farrar Browne is a satirical travelogue written during the late 19th century. The book chronicles Browne's humorous adventures as he journeys from New York to California and back, narrated through the lens of his comedic alter ego, Artemus Ward. Throughout the tale, he captures the quirks of fellow travelers, the chaos of traveling by steamer, and the oddities of various locales, offering a blend of social commentary and wit. The opening of this installment introduces readers to the chaotic scene aboard the steamer Ariel as it embarks for California. As passengers clamored to board, Browne humorously depicts his frantic search for his belongings amidst the bustling crowd. He shares amusing anecdotes about his interactions with fellow travelers, including a sweet young lady who accidentally confuses him for someone named George, and comically critiques the awful conditions aboard the still crowded and poorly managed vessel. These relatable experiences set the tone for Browne's comedic observations that will follow in his exploration of various regions, from the Isthmus of Panama to California, highlighting the absurdities of travel and the eclectic people he encounters along the way. (This is an automatically generated summary.)s
Release date is 2002-06-01
This etext was produced by anonymous Project Gutenberg Volunteers
Keywords: American wit and humor